Pengaruh Jenis Pupuk dan Tinggi Genangan terhadap Pertumbuhan dan Konsumsi Air Tanaman Padi (Oryza sativa L.) Varietas Padi M70D - Ridwan, Ridwan; Amin, Muhammad; Shelani, Indah Sekar; Rosadi, R.A Bustomi (abe.fp.unila.ac.id, 2022)
Food security improvement program is directed to be able to fulfil the food needs of people in the country from national food production. One of the national foodstuffs that is strived to be provided throughout the year is rice. The purpose of this study to obtain flooding height and type of fertilizer that can provide maximum M70D rice production and improve soil fertility. This study uses a completely randomized design (CRD) arranged in factorial 2x4 with three replications. The first factor is the application of water level consisting of 4 levels including (2 cm, 3 cm, 4 cm, and 5 cm). The second factor is the application of fertilizers consisting of ghally organic and Urea, TSP, and KCL fertilizers. The results showed that in general the treatment of 4cm flooding height and Urea, TSP, KCL fertilizer gave the best results on plant height, number of tillers, number of productive tillers, and number of rice grains. Meanwhile the treatment of ghally organic fertilizer can increase nutrients in the soil and rice plants. Ghally organic fertilizer has more role to improve soil structure and more efficient on water consumption of M70D rice plants. M70D rice plants cannot be applied by ghally organic fertilization using the spread method, because ghally organic fertilizers based on aerobic and anaerobic microba which can not work optimally in flooded conditions. Keyword: Fertilizer, Flooding Height, Nutrient, Paddy.